2014
DOI: 10.1155/2014/372503
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Bovine Viral Diarrhea Virus E0 Protein in Transgenic Astragalus and Its Immunogenicity in Sika Deer

Abstract: The bovine viral diarrhea virus (BVDV), a single-stranded RNA virus, can cause fatal diarrhea syndrome, respiratory problems, and reproductive disorders in herds. Over the past few years, it has become clear that the BVDV infection rates are increasing and it is likely that an effective vaccine for BVDV will be needed. In this study, transgenic Astragalus was used as an alternative productive platform for the expression of glycoprotein E0. The immunogenicity of glycoprotein E0 expressed in transgenic Astragalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…ELISA was employed to detect the expression of glycoprotein E rns in transgenic hairy roots [ 41 ]. Briefly, the extracts were incubated in the ELISA plate at 4°C overnight, followed by 3 washes with PBST, and blocking with 10% horse serum for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA was employed to detect the expression of glycoprotein E rns in transgenic hairy roots [ 41 ]. Briefly, the extracts were incubated in the ELISA plate at 4°C overnight, followed by 3 washes with PBST, and blocking with 10% horse serum for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The soluble proteins prepared from control and transgenic plants were analyzed by Western blot as previously described [ 41 ]. The extracted total soluble proteins from fresh transgenic hairy roots were subjected to electrophoresis on 12% sodium dodecyl sulfate polyacrylamide gel (SDS-PAGE) and transferred to a nitrocellulose membrane (GE Healthcare, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated, in some cases, only empirical data can be relied upon to determine the appropriate virus surface charge because published isoelectric points of some capsid proteins may not be suitable for determining the total charge of the virus [41][42][43]. Nevertheless, in one of the chromatographic and other isoelectric points studies it was shown that some LEVs (MuLV, BVDV) displayed an overall net negative charge above pH 6 and a positive net charge below pH 6 [41,42], whilst most NLEVs were positively charged at a pH below 7 and negatively charged at a pH above 7 [43]. It means that under inactivation buffer pH 7.2 in our experiments LEVs will have a weak positive charge and will interact with strong negative charge of WorkBeads 40S and their elution will braked by gel.…”
Section: Direct Virus Inactivation By S/d Treatment During Fviii/vwf mentioning
confidence: 99%